2014
DOI: 10.1039/c3cc49588d
|View full text |Cite
|
Sign up to set email alerts
|

Fast Li-ion conduction in poly(ethylene carbonate)-based electrolytes and composites filled with TiO2 nanoparticles

Abstract: We have found remarkable ion-conductive properties in a novel polymer electrolyte composed of poly(ethylene carbonate) and Li bis-(fluorosulfonyl) imide. The self-diffusion coefficient of Li-ions exceeded 10(-7) cm(2) s(-1) and the Li transference number was estimated to be more than 0.8 in composites filled with only 1 wt% of TiO2 nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
265
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(285 citation statements)
references
References 27 publications
20
265
0
Order By: Relevance
“…2(b) presented the temperature dependence of ionic conductivity for PDEC-LiTFSI and PTEC-LiTFSI electrolytes. It could be observed that the temperature dependence agreed well with the Arrhenius equation over the range of C. These electrolytes behaved like the poly(ethylene carbonate) based electrolytes due to similar chemical structures, which was in good accordance with the previous reports by Tominaga [46,47]. The ionic conductivity of PDEC-LiTFSI was 3.81 Â10 À6 S cm À1 at 25 C and 8.11 Â10 À5 S cm À1 at 80 C, respectively.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…2(b) presented the temperature dependence of ionic conductivity for PDEC-LiTFSI and PTEC-LiTFSI electrolytes. It could be observed that the temperature dependence agreed well with the Arrhenius equation over the range of C. These electrolytes behaved like the poly(ethylene carbonate) based electrolytes due to similar chemical structures, which was in good accordance with the previous reports by Tominaga [46,47]. The ionic conductivity of PDEC-LiTFSI was 3.81 Â10 À6 S cm À1 at 25 C and 8.11 Â10 À5 S cm À1 at 80 C, respectively.…”
Section: Resultssupporting
confidence: 78%
“…These results were much superior to the PEO based lithium batteries [60] and comparable to the PEC and P (CL-co-TMC) based lithium batteries [46,47,49]. The rate capability of the Li/LiFePO 4 cell from 0.1C to 0.5C at 55 C is presented in Fig.…”
Section: à2mentioning
confidence: 61%
See 2 more Smart Citations
“…It is now fairly routine to report both σ and t +,SS of newly-developed polymer electrolytes. 41,44,45,47,48,[58][59][60] The question of limits on i ss /i 0 , or equivalently, t +,SS is an interesting open question. While most papers have reported i ss /i 0 values between 0 and 1, there is at least one report wherein i ss /i 0 obtained from an electrolyte was greater than 1.…”
mentioning
confidence: 99%